Mini-Review: GSDME-Mediated Pyroptosis in Diabetic Nephropathy - Li, Wen; Sun, Jing; Zhou, Xiaoxi; Lu, Yue; Cui, Wenpeng; Miao, Lining (Frontiers in Pharmacology, 2021)
Pyroptosis is a recently identified type of lytic programmed cell death, in which pores form in the plasma membrane, and cells swell, rupture, and then release their contents, including inflammatory cytokines. Molecular studies indicated that pyroptosis may occur via a gasdermin D (GSDMD) and caspase-1 (Casp1) -dependent classical pathway, a GSDMD and Casp11/4/5-dependent non-classical pathway, or a gasdermin E (GSDME) and Casp3-dependent pathway. Studies of animal models and humans indicated that pyroptosis can exacerbate several complications of diabetes, including diabetic nephropathy (DN), a serious microvascular complication of diabetes. Many studies investigated the mechanism mediating the renoprotective effect of GSDMD regulation in the kidneys of patients and animal models with diabetes. As a newly discovered regulatory mechanism, GSDME and Casp3-dependent pyroptotic pathway in the progression of DN has also attracted people’s attention. Z-DEVD-FMK, an inhibitor of Casp3, ameliorates albuminuria, improves renal function, and reduces tubulointerstitial fibrosis in diabetic mice, and these effects are associated with the inhibition of GSDME. Studies of HK-2 cells indicated that the molecular and histological features of secondary necrosis were present following glucose stimulation due to GSDME cleavage, such as cell swelling, and release of cellular contents. Therefore, therapies targeting Casp3/GSDME-dependent pyroptosis have potential for treatment of DN. A novel nephroprotective strategy that employs GSDME-derived peptides which are directed against Casp3-induced cell death may be a key breakthrough. This mini-review describes the discovery and history of research in this pyroptosis pathway and reviews the function of proteins in the gasdermin family, with a focus on the role of GSDME-mediated pyroptosis in DN. Many studies have investigated the impact of GSDME-mediated pyroptosis in kidney diseases, and these studies used multiple interventions, in vitro models, and in vivo models. We expect that further research on the function of GDSME in DN may provide valuable insights that may help to improve treatments for this disease.